Didactic strategy to improve the vocabulary of english by establishing the differences between american and british english - Lucas Estupiñan, Emily Estefania (Machala, Utmachala, 2023)
The following research was carried out in order to investigate the possible causes of the deficit of vocabulary in English in the variant of British English. present in the students of the sixth year of the School of Private Basic Education "Nueva Aurora" an educational institution machaleña and in the same way offer the educational community a viable solution to deal with the problem. In such a way that the insertion of a didactic strategy is offered to improve the vocabulary of English by establishing the differences between American and British English. The research delves into the use of didactic strategies and application in language teaching through a quantitative approach of explanatory type and experimental design
La siguiente investigación se llevó a cabo con la finalidad de indagar el las posibles causas del déficit de vocabulario presente en los estudiantes del sexto año de la Escuela de Educación Básica Particular “Nueva Aurora” una institución educativa machaleña y de la misma manera ofrecerle a la comunidad educativa una solución viable para tratar la problemática, de tal manera que se oferta la inserción de una estrategia didáctica para mejorar el vocabulario del inglés estableciendo las diferencias entre el inglés americano y británico. La investigación ahonda en el uso de estrategias didácticas y aplicación en la enseñanza de idiomas mediante un enfoque cuantitativo de tipo explicativo y diseño experimental.
Keywords: DIDACTIC STRATEGY; VOCABULARY; ENGLISH; IMPROVEMENT; DIFFERENCES; INSERTION